Relationship between sleep and myopia among primary and secondary school students with different durations of outdoor activities in Beijing: a cross-sectional survey - Jingshu ZHANG; Ting LI; Han YANG; Ran QIN; Hai ZHAO; Lu WANG; Bingjie SUN; Xin GUO (Zhongguo gonggong weisheng)
ObjectiveTo analyze the relationship between sleep and myopia in primary and secondary school students with different durations of outdoor activities in Beijing, aiming to provide an evidence for myopia prevention and control in the students. MethodsFrom September to December 2021, 24 326 students recruited using stratified random cluster sampling from 16 districts in Beijing municipality underwent visual acuity testing and an on-site anonymous online questionnaire survey. A multivariate logistic regression model was used to analyze the relationship between sleep duration and myopia in students with different durations of outdoor activities. ResultsOf the 22 957 valid participants, 71.6% were identified as having myopia, 61.0% reported insufficient time spent outdoors, and 70.0% reported insufficient sleep. The prevalence of myopia was higher in participants with insufficient sleep than in those with sufficient sleep (73.6% vs. 67.2%, χ2 = 96.970; P < 0.001). Multivariate logistic regression analysis showed that after adjustment for gender, urban/rural residence, education level, parental myopia, daily after-school study time, daily TV viewing time, daily screen viewing time, and whether they turn off the light when viewing screens after dark, among participants who reported insufficient time spent outdoors, those with insufficient sleep had an increased risk of myopia (odds ratio = 1.10, 95% confidence interval: 1.03 – 1.18; P < 0.05) compared to those with sufficient sleep; subsequent gender stratification analysis showed that the risk of myopia was increased in male and all participants, but not in female participants. ConclusionAmong students with inadequate outdoor activity, the prevalence of myopia was higher among those with inadequate sleep, suggesting that parents and teachers should encourage students to participate in more outdoor activity and ensure adequate sleep to reduce the risk of myopia.